The “Gryfice Scandal” In Poznań — Dealing with Abuses Committed in the Process of Establishing Cooperative Farms in the Poznań Region - Jankowiak, Stanisław (Studia Historiae Oeconomicae, 2017)
Several years after the war, a revolution started in the Polish agriculture - even though until 1948, the authorities claimed that farms in Poland would not be collectivized. The new stage meant that things accelerated quickly. Central party authorities determined the number of cooperatives to be established per year in a top-down manner. The Poznań region was considered particularly opposed to the system, hence the pressure to establish cooperative farms was particularly intense. The quick pace of the operation and accountability of the party officials for its results meant that they often resorted to prohibited methods of forcing resistant individuals to enter into cooperatives. Though party guidelines emphasized that the process was voluntary, and formally banned any form of pressure, various forms of power abuse were tolerated in practice. Only when the situation rapidly escalated into scandals, the authorities stigmatized the illegal methods. However, after a while, the situation returned to normal, and the anomalies reoccurred. The problem was that the principles of the operation were flawed. One of the party activists claimed that establishing cooperatives according to the guidelines would have taken 200 years to complete. Farmers had to be coerced, otherwise they would never have joined cooperatives. Most cooperative farms established this way collapsed in 1956.